Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 1342921103 species occurrences available in GBIF matching the query: null The dataset includes 1342921103 records from 25066 constituent datasets: 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 18 records from Naturtag. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 607514 records from Plant. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 6192 records from marine sediment metagenome Metagenome. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2812 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 10654 records from Bryophyte specimens of The Nagoya University Museum. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 5514 records from MCP-Aves - Coleção de Aves. 265 records from Nannofossil abundance of Hole 36-329. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 13 records from Dinoflagellate abundance of Hole 14-144. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1158 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 20 records from Planktic foraminifera abundance of Hole 19-185. 50 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 1266 records from A Catalogue and Historical Study of the Odonata of Ecuador. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 5 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 243 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 480819 records from KTP Ring Data. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 196 records from Collection des mammifères d'Auvergne. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 48 records from Morphologische Daten von Natrix. 12645 records from Brown University Herbarium. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 89 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 98 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 1217 records from 16S rRNA metagenomic investigation of arsenotrophic bacteriome of ground water and soil from arsenic-prone area of Bangladesh. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 8 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 201 records from Biodiversity of springs and rock seepages 2003. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 42 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 1862 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 1049 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 7123 records from DMNS Egg Collection (Arctos). 9404 records from MZL Invertebrate Collections. 1303 records from Crustacean specimens of Bihoro Museum. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 170 records from Total foraminifera counts of multinet SO117_MSN1244. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 3435 records from Benthos Chirnov Basin 1986 and 2002. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 51 records from Coccoliths in sediment core GIK23065-3. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1004 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 26159 records from NBN - Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 12 records from Analyses of the recent components of sediment core PS1219-1. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 339 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 120 records from BIRDRACE The early birds. 203916 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 92 records from Protozoa Abundance_Microbial Parameters. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 21884 records from Birds Specimens. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 115 records from Antarctic Pycnogonids II. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 6979 records from Upper Silesian Museum, Bird Observations. 56 records from Planktic foraminifera abundance of Hole 23-227. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 19147 records from DMNS Mammal Collection (Arctos). 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 126 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 1519 records from IBF Monitoring of Fungi. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1809 records from BenthosChukchiFN762_1976_Falk5. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1054 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 234 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 254 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 69 records from BIRDRACE Pfeifenten. 51 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 6158 records from Marine metagenome ICM_JRV. 5000 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 240 records from Knechtweide (Kohlfurth). 322 records from Collections ichtyologiques et herpétologiques (BOUM). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 1584 records from MCP-Mamiferos - Coleção de Mamíferos. 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 276 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 308 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 6192 records from NE Scotland fish records 1800-2010. 224 records from Natura 2000 PnrL. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 270 records from bmhs_weatherheadshell_collection. 205 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2498 records from Helmintos parásitos de peces del sureste de México. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 4 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3340 records from Palaeobiology collection, FAU Erlangen. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 30 records from Planktic foraminifera abundance of Hole 14-144. 413272 records from DATAVES. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 7 records from Planktic foraminifera abundance of Hole 53-418B. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 24283 records from Berea College, Ralph L. Thompson Herbarium. 424 records from Distribution of nanoplankton at trap WR2. 79 records from Birdrace-Bielefinken-Bielefeld. 125 records from Range table from ostracoda in ODP Hole 143-866B. 7446 records from Fish specimens of Toyama Science Museum. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 6004 records from Colección Limnológica Universidad de Antioquia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 181857 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 3529 records from A dataset from bottom trawl survey around Taiwan. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 27108 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 144 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 95 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 30008 records from Lepidoptera specimen database of Japan. 308173 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 68 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 130 records from BIRDRACE - The famous Grouse feat. The James. 374 records from Planktic foraminifera abundance of Hole 68-503B. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 45 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 906 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 603 records from Nannofossil abundance of Hole 37-334. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 59 records from Schulgelände SGD/Viersen. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 42 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 12859 records from Colecção Entomológica IIA. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 17155 records from MZFC/Coleccion de Aves. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 2787427 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 31 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 1513 records from M. Gollop Collection. 53204 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 18 records from Schulgarten der Gesamtschule Am Heidberg. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 515 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 81329 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 35 records from Reptiles Specimens of Akita Prefectural Museum. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 339 records from UWIZM Snakes. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 412 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 291402 records from ARABEL - Arachnologia Belgica. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 348 records from Antarctic pycnogonids. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 62776 records from MLZ Bird Collection (Arctos). 449 records from Artsprosjekt Pyrenomycetes. 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 2421 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 7471 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 68396 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27264 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 1 records from A new African Apiocera species (Apioceridae, Diptera). 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 1271 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 127 records from Сypripedium guttatum Sw. in the Komi republic. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 8 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 79 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 124 records from Kirkliston Range stream monitoring. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 39 records from Planktic foraminifera counts of sediment core V19-21. 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 5361 records from Colección Ornitológica de la Universidad del Valle. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 77 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 324 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 172 records from Total foraminifera counts from multinet M31/3_MSN915. 975046 records from NatureServe Network Species Occurrence Data. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 4 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 215 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 26050 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 353 records from Données naturalistes de Hubert GUIMIER. 1728 records from Collection rousset -1947-2013. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 6 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 114001 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 105857 records from Fish specimens of Kagoshima University Museum. 39345 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13647 records from UTEP Invertebrates (Arctos). 21 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1941 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3078 records from Insectes Hyménoptères Scollidés de France. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 828 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 3 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 17 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 15 records from Nannofossil abundance of Hole 10-93. 7527 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 14 records from Occurrence of mammalia relicts at site Climauti II. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 142 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 263 records from Planktic foraminifera counts of sediment core V14-77. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 135 records from Waldi-Weiher. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 3724 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 389 records from Amphibian and Reptilian (KIEE-AR). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 41676 records from Tagged Seal Location Data from SOGLOBEC. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 333 records from Données naturalistes de Renaud PUISSAUVE. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 881 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 4 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1709 records from The Gibson spider collection. 67 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 651 records from Réseaux écologiques/Trame verte et bleue. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 29 records from Herbarium Senckenbergianum (FR) - Protista. 66164 records from Florida Keys Reef Visual Census 1996. 3 records from Zoology in the Middle East. 2867 records from Pollichia Pilzherbar. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 24387 records from Données de Luc BARBARO. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 280 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 218 records from Nannofossil abundance of Hole 49-408. 874 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 11 records from Analyses of the recent components of sediment core PS1011-1. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9810 records from Royal British Columbia Museum Entomology Collection. 106 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 25 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 477 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 6 records from Foraminifera abundance of Hole 58-442. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 27810 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 205252 records from National Benthic Inventory. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 22586 records from Tachinid Recording Scheme - GB and Ireland records. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 27 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 4617 records from Données de type contact de Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 14566 records from Canadian Museum of Nature Palynology Collection. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 223486 records from Phytochorologie des départements français. 89 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 2 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 55 records from Galls on Beech Trees in Hainich, 2008. 8 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 244406 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 9 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 321633 records from Seasearch Marine Surveys in England. 38 records from Planktic foraminifera abundance of Hole 84-566C. 2289 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 648 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 569 records from Pollen analysis of sediment core GeoB6518-1. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 108313 records from Arizona State University Hasbrouck Insect Collection. 39 records from Planktic foraminifera abundance of Hole 27-260. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 34 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 53 records from Relative abundance of planktic foraminifera in sediment core K11. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 1 records from Planktic foraminifera abundance of Hole 54-420A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 22 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 4764 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 351 records from UWYMV Herpetology Collection (Arctos). 4585 records from Marine bacteria Targeted Locus (Loci). 292 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 14069 records from Midden-Limburg Fish Ponds Survey. 240635 records from Dataflos. 26 records from Halocosa gen. n., a new genus of Lycosidae (Araneae) from the Palaearctic, with a redescription of H. cereipes (L. Koch, 1878). 175 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 2746 records from marine sediment metagenome Raw sequence reads. 104498 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 34 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 3 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 3 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 34332 records from Protist Diversity in the East China Sea. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1715185 records from NBIS Records to December 2016. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 173 records from Fundación Miguel Lillo - Colección Invertebrados. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 30 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 931 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 3 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 1900 records from Fungi Collection. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Thirteen new records of ferns from Brazil. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 435 records from Marine metagenome ICM_AWP. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202388 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 4 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40281 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 179 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 120 records from Total foraminifera counts of multinet M10/2_MSN262. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 26 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6336 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 282 records from Deponie Klausdorf. 48 records from Schulgelände (Wetter). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 558 records from Foraminifera abundance of Hole 74-526A. 59 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 61 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 31 records from Benthic foraminifera abundance of Hole 42-379A. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipaility – Norway; 1996 – 2017 based on systematic catches with ordinary mouse traps in traplines. 1333 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2548 records from BioGIS - Reptiles - HUJ collections. 10 records from Analyses of the recent components of sediment core PS1222-1. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 237 records from Planktic foraminifera abundance of Hole 21-207. 650217 records from Flora Atlas N.T.. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 54 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 1597 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1191 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 10 records from Ostracoda abundance of Hole 32-306. 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 630 records from Nannofossil abundance of Hole 29-281. 8069 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Rare plants database extract from Scottish Natural Heritage. 413 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 15759 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 3 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (München). 146 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle RNC:102. 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 209 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9150 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 2 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 9 records from Nannofossil abundance of Hole 2-11. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 180 records from Données naturalistes de Pascal Dupont. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 130 records from Faunal assemblage of sediment core GS7603-13. 437 records from Bird specimens of Bihoro Museum. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 15 records from Nannofossil abundance of Hole 6-48B. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 5515 records from Colección de Anfibios. 11143 records from NBMB Herps. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 386 records from Foraminifera distribution of sediment core KS310. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 138 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1036 records from BUND - Dassower See (Lübeck/Dassow). 102 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 70 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54402 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 152253 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40218 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 6 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 28 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1001 records from Mushroom (KIDR-MR). 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 2 records from Benthic foraminifera abundance of Hole 42-376. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1 records from Description of females of Chilarboreus Ruta, 2011 (Coleoptera: Scirtidae: Scirtinae). 401 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 242 records from UTEP Fish (Arctos). 7 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 2799 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 128 records from Faunal assemblage of sediment core TR149-32. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 1000 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 1 records from Hoplophora ardua. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 190 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 111 records from Birdrace-Uhulogen-Lippe. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7128 records from La familia Asclepiadaceae en México. 46 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 14981 records from JOI - Herbário Joinvillea. 31 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 3 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 2360 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 103 records from Mammals (UWEP-MM). 9 records from Benthic macrofauna abundance of sediment core 12930-048. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1215 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 15 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 276 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 675 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 72399 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1383 records from Plant observations from Białowieża National Park. 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 85277 records from University of Ghana - Ghana Herbarium. 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 2 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 14 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1943 records from Pollen profile RAC20, Lake Racou, France. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 10898 records from Inventario de Hymenóptera; parasítica en México. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 7462 records from Ibaraki Nature Museum, Fungi collection. 1798 records from 3Soil16S. 924 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 181977 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 32 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 68 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 55 records from Dinoflagellate abundance of Hole 28-274. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 312 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 33419 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 495 records from Planktic foraminifera counts of sediment core A15-558. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 1165 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 557 records from Corn bunting breeding distribution in Scotland. 7122 records from Whale catches in the Southern Ocean. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 3171 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 145 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 1047 records from NZCS Invertebrates New Collection After 1987. 3005 records from Colección Entomológica CDMB. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 11258 records from Uncultured eukaryotes Targeted Locus (Loci). 16933 records from Lepidoptera (Specimens NRM). 407 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 2 records from Waidelotinae, a new subfamily of Pyrochroidae (Coleoptera: Tenebrionoidea) from Baltic amber of the Sambian peninsula and the interpretation of Sambian amber stratigraphy, age and location. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 1644 records from Las comunidades de myxomicetes de selva baja caducifolia. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 84981 records from NINA Vanndata fisk. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 31 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 510 records from Inventaires des cygnes du département de l'Eure. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 61 records from Alien Species in Poland - Plants. 53062 records from British Antarctic Survey Argos satellite tracking data. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 1 records from Zetes pallidulus. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 114 records from Total foraminifera counts of multinet M26/1_MSN844. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 14 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 5 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 3415 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 5 records from On some species of the genus Acrolocha Thomson, 1858 of the Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1197 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 197 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 12761 records from Données naturalistes de Franck NOEL. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 343 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2 records from Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features. 3327 records from BioGIS - Mammals - SPNI. 91840 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 7 records from Revision of Sinonereis Wu & Sun, 1979 (Annelida: Nereididae). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 1 records from Redescription of Amerila abdominalis (Rothschild, 1933), a little-known species of tiger moth from Southeast Asia (Lepidoptera: Erebidae: Arctiinae). 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 120 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 141 records from Total foraminifera counts from multinet SO119_MSN1285. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 170 records from Planktic foraminifera abundance of Hole 94-610B. 77414 records from MfN - Fossil vertebrates IV. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 1 records from Solving a long-standing nomenclatorial controversy: designation of a neotype for the southern sea lion Otaria flavescens (Shaw, 1800). 3 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 3304 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 322193 records from Florida Keys Reef Visual Census 2010. 14 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 153 records from annex1. 132 records from Total foraminifera counts of multinet POS247/2_MSN1377. 35 records from Dinoflagellate abundance of Hole 28-270. 1 records from Nothrus bicarinatus. 10 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 2268 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 52443 records from Extracellular DNA marine sediment Targeted Locus (Loci). 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 164 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 8328 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 28385 records from Plan de vertebrados de la Patagonia. 25 records from Fleas (Siphonaptera) of Turkey: species composition, geographical distribution and host associations. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 3131 records from AlgaTerra. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Occurrence of mammalia relicts at site Igstadt I. 268 records from Planktic foraminifera abundance of Hole 22-217. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 7326 records from MfN - Fossil vertebrates III. 8 records from Nannofossil abundance of Hole 39-353A. 16988 records from LPO_PACA_2017_12_18. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 60 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 8633 records from HSU Vertebrate Museum Mammals Collection. 23 records from Nannofossil abundance of Hole 9-80. 37480 records from ADDOMEx. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 127 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 343 records from Foraminifera abundance of Hole 57-440B. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6768 records from Coral or reef-seawater associated bacteria Targeted Locus (Loci). 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 6 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 8408 records from UTEP Insects (Arctos). 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 27 records from A new genus and two new species in the tribe Selizini (Hemiptera: Fulgoromorpha: Flatidae) with a checklist for the tribe from China. 4 records from Sächsische Schweiz (Wehlener Gebiet). 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 5 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 211452 records from University of Michigan Museum of Zoology, Division of Birds. 40 records from Planktic foraminifera abundance of Hole 14-137. 7 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 2404 records from UWYMV Bird Collection (Arctos). 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 2645 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 623 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 1000 records from Collection Graptolithina fossil SMF. 11 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 82649 records from Specimen Database of Colorado Vascular Plants. 1288808 records from PlutoF platform observations. 25953 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 13 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 62 records from Zoo Frankfurt. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 1085628 records from Fungal Records Database of Britain and Ireland. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 45 records from Nannofossil abundance of Hole 10-89. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 1112 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61999 records from La familia Asteraceae en México. Fase VI. 356 records from Morphologische Daten von Puffinus creatopus. 610 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 23648 records from WTSWW Data: All Taxa (West Wales). 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2312 records from Mycological collection of the National Museum. 63 records from Marine gastropod distribution from patagonian shallow waters. 6 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 148 records from Herbarium BSG Hepaticopsida. 21 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 1 records from Two new species of obligatory termitophilous rove beetles from Brazil (Coleoptera: Staphylinidae: Termitomorpha Wasmann). 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 203 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 69 records from Unter hellen Zinnen und finsteren Grotten. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 80 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6172 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6446 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 47 records from Données d'observation de phanérogames marines en Martinique. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 86 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 374 records from Coastal and Marine Species Database. 190 records from Nannofossil abundance of Hole 67-499. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 127 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ulf Soltau. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 15 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 10 records from Données naturalistes de DURON Cyril. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28408 records from Collection Pisces SMF. 60916 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 98 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 442 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 12 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 262 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 316 records from Planktic foraminifera abundance of Hole 42-375. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 96 records from Planktic foraminifera abundance of Hole 32-305. 17 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 84 records from Total foraminifera counts from M35/1_MSN1051. 1514 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 203 records from Nannofossil abundance of Hole 67-496. 525 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 852 records from OMMAG_Suivi_Dauphins_Les_Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 1402 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 41 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 368 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 235 records from Pollen and spore abundance of Hole 42-381. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 251297 records from Estonian Nature Observations Database. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 270171 records from Biodiversitätsdatenbank des Landes Salzburg. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 17713 records from NCSM Mammals Collection. 17 records from Nannofossil abundance of Hole 52-418. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 97 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 28 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 27947 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 6 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 4 records from Gynacantha vargasi (Odonata: Anisoptera: Aeshnidae) sp. nov. from Costa Rica. 10 records from First record of the spider genus Wolongia Zhu, Kim & Song, 1997 from India with the description of a new species (Araneae, Tetragnathidae). 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 1 records from Amycolatopsis marina sp. nov., an actinomycete isolated from an ocean sediment. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 12418 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 27 records from Planktic foraminifera abundance of Hole 18-174. 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 12217 records from California State University, Long Beach Mammals. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 5071 records from Données de mammifères enregistrées dans BazNat - Lot 2. 92 records from Nottekanal, Klasse 7 - 10. 84 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 106 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 261 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 4845 records from Inventaire des Mollusques Sphaeriidae de France. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3687 records from Clare Biological Records Centre Dataset 2004-2007. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 884 records from Sea shells of New South Wales. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 16 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 27476 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 2 records from A contribution to the revision of Adorodocia Brenske (Coleoptera: Scarabaeidae: Rutelinae: Adoretini): a new peculiar species from Ankaratra, Madagascar. 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 30 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 20 records from Truchas Mexicanas. 50 records from Flora und Fauna im Brexbachtal. 13646 records from Senckenberg - CeDAMar Resource. 51 records from Marine metagenome ICM_VAG. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 5 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 802 records from Biological Collection, National Institute of Oceanography, Goa, India. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 1579 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 1016 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 828 records from Insect specimens of Natural History Museum, Kishiwada City. 38 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Corvidae. 173 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 17 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 4507 records from ARC-PPRI: National Collection of Insects: Coleoptera Collection (1879-2012). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 46074 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 9304 records from Echinoderm collection of National Museum of Nature and Science. 430 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 109176 records from Herps Specimens. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 39295 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 10698 records from Yoann_BLANCHON_2017_12_18. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14853 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 638313 records from Données de la flore d’Alsace (SBA). 13 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 3 records from MSB Mammal Observations (Arctos). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 61718 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Données naturalistes de Sophie COHEN. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 54 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 4091 records from Wikiplantbase #Sicilia. 1153 records from Nannofossil abundance of Hole 17-167. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 2657 records from Database of Australasian Vertebrate Occurrences. 289 records from bmhs_butterfly_collection. 498 records from Bekkelag basin, Inner Oslofjord. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3817 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 633 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 62 records from Benthic foraminifera abundance of Hole 42-380. 172 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1142431 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 96 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 57 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 3 records from A new genus and new species of Potamidea (Crustacea: Decapoda: Brachyura: Potamoidae), the first stygomorphic cave crab known from China and East Asia. 61473 records from EAC - Herbário Prisco Bezerra. 29105 records from Marine Biological Sample Database, JAMSTEC. 91 records from CNIN/Tipos Homoptera. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 328 records from Otter (Lutra lutra), Outer Hebrides. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 30213 records from Collection Crustacea - ZMB. 874 records from The Living Murray Fish data. 742 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4429 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 1128 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 246 records from BARTH-Environnement_2017_12_18. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 162 records from Total foraminifera counts of multinet M21/2_MSN658. 109 records from MMFR Zingiberaceae Botanical. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 31 records from Nannofossil abundance of Hole 9-82. 25 records from Microzooplankton abundance and biomass at station TT043_11-1. 2082 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 101 records from BIRDRACE Enger am Spektiv. 3803 records from Ghent university - Zoology Museum - Nematod Collection. 54 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 131 records from Total foraminifera counts from multinet M32/3_MSN956. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 6170 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Groß Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 153 records from Planktic foraminifera abundance of Hole 18-181. 108 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 1 records from Naiadacarus sidorchukae sp. n. (Acariformes: Acaridae) from Western Siberia closely related to a North American species, with a new generic synonymy. 101 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 96 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 38 records from Was lebt in der Brutzwiese?. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 1 records from Planktic foraminifera abundance of Hole 54-428. 519 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 9 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 14 records from Benthic macrofauna abundance of sediment core 13200-045. 6776 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 1 records from On the Chilopoda from Turkey. 2284 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 271 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 440 records from Wichita State University Collection. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 2336 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 61 records from Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae). 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 2159 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 9 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 24907 records from Insect specimens of Himeji City Science Museum. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 2412 records from Ohio University Invertebrate Paleontology Collection. 3477 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 4 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 281 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Subterranean millipedes (Diplopoda) of the Iberian Peninsula. 1 records from Oppia nitens. 24 records from Tanzanian Vertebrate Collection. 32 records from Occurrence of mammalia relicts at site Bettelküche. 30 records from An annotated catalogue of the gamasid mites associated with small mammals in Asiatic Russia. The family Haemogamasidae (Acari: Mesostigmata: Gamasina). 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 145 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 5118 records from Fish specimens of Natural History Museum, Kishiwada City. 603 records from Fossil (NSMK-FO). 11 records from Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae). 5823 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 1440 records from Abundance of algae in the Aral Sea. 29 records from Naturerfahrung. 60 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 2502 records from ISM Herpetology Collection. 378 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 3210 records from HerbarioHerrerense. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 9 records from Dinoflagellate abundance of Hole 71-513A. 50682 records from CZE National PGR Inventory. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 203 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 243 records from Thistles species and abundance. 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 204 records from Total foraminifera counts of multinet SO118_MSN1253. 2 records from Notes on two rare conger eel species (Anguilliformes: Congridae) found in Taiwanese waters. 6288 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 13947 records from The Vascular Plants Collection of the University of Goettingen. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 24 records from A new species of Pseudobunocephalus Friel, 2008 (Siluriformes: Aspredinidae) from the lower Tocantins and Mearim river drainages, North and Northeast of Brazil. 1278 records from Foraminifera abundance of Hole 45-396. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 755529 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 9 records from A new species of Leptobrachella (Anura: Megophryidae) from southern Guangxi, China. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 1125 records from Données naturalistes de Stéphane ORIO. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 182790 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 665 records from Collection Echinodermata - ZMB. 260 records from Miljodir_naturtypekartlegging_2017. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 7 records from Revision of Thaumatocranaus Roewer, 1932, with description of two new species (Opiliones: Laniatores: Gonyleptoidea). 244 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 391 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 3714 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 22 records from A new subspecies of Glabroculus elvira (Eversmann, 1854) (Lepidoptera, Lycaenidae) from the Dzhungarian Gobi desert, Mongolia. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 4 records from New fossil taxa of Ischalia Pascoe (Coleoptera: Ischaliidae) from Eocene Baltic amber. 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 20890 records from CPAP - Herbário CPAP. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 448 records from Harpactus Shuckard. 2500 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 41 records from List of Snail species in Vava'u. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jardín Natural Reserve, Quindío, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 3 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 128 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 26918 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 5 records from Schulinnenhöfe (Gelsenkirchen). 4 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 18 records from Predatory Dinosaurs of the World. 770 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 3294 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 814 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 721 records from Nannofossil abundance of Hole 64-476. 16685 records from Colección general del plantas vasculares del Herbario JBB. 2875 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 53 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 1863 records from Cowan Tetrapod Collection - Herpetology. 170 records from Total foraminifera counts from multinet M31/3_MSN898. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 678 records from Upper Silesian Museum, Bird Collection. 197 records from Phytoplankton abundance at station CD46_0705C#4. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 3 records from New synonymies in the plant bug family Miridae (Hemiptera: Heteroptera) from Northern China. 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 1139 records from Shellfish (MNHM-MS). 29 records from Hemmerder Schelk (Unna). 50 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 10 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 151 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 16 records from jamaica_invasive_alien_species. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 65 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 7814 records from Odonata de Veracruz. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 478 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 7548 records from Botanic Garden of the Finnish Museum of Natural History. 89 records from Planktic foraminifera abundance of Hole 63-470A. 1873 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 901 records from The Masao Oita Insect Collection of The University Museum, The University of Tokyo. 55 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 157 records from Loup 2009 présence régulière communale (réseau Loup-Lynx ONCFS). 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 59 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10484 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 300 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 1 records from Ubristes rex sp. n., a new microdontine hoverfly from northern Brazil (Diptera: Syrphidae: Microdontinae). 39 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16506 records from Database for alien invasive plants occurrences in Germany. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 2 records from Arthropoden aus südostalpinen Höhlen.. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 80 records from Foraminifera distribution of sediment core SDSE189. 10212 records from Spider (NSMK-SP). 2967 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 14590 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 3 records from Two new species of the Simulium (Simulium) tuberosum species-group (Diptera: Simuliidae) from Palawan, the Philippines. 1432 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 88 records from "Schlechteberg" Ebersbach/Sa.. 9519 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 374 records from Medicinal potential of African plants (Togo). 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 4484 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 2 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 136 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 42 records from Nannofossil abundance of Hole 1-3. 278 records from MfN - Fossil invertebrates IIa. 89 records from A Synopsis of the Odonata (Dragonflies) of Sumatra. 611 records from Planktic foraminifera counts of sediment core V29-64. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 27351 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 193 records from Loup 2009 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 11253 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 13096 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 1 records from Arthropoden aus südostalpinen Höhlen.. 224 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 536 records from Kieppi bird collection. 10 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 1296 records from Plant specimens of the Museum of Yamagata University. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 20945 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 18 records from Biodiversidad en el valle de Cuatro Ciénegas.. 17 records from Peces de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 113 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 265002 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 173415 records from Hymenoptera specimen database of Kyushu University. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 1 records from Thismia nigricoronata, a new species of Burmanniaceae (Thismieae, Dioscoreales) from Vang Vieng, Vientiane Province, Laos, and a key to subgeneric classification. 774949 records from Finnish Floristic Database (Literature Sources). 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 3148 records from Ross A. Layberry, Collection. 1 records from Ascidians collected during the Madibenthos expedition in Martinique: 1 - Phlebobranchia. 4 records from Notomicrus petrareptans sp. n., a new seep-dwelling species of Noteridae from Suriname (Coleoptera: Adephaga). 2 records from Evaluating the generic definition of Lithopolia Yoshimoto, 1993 with a description of one new species of Taiwan (Lepidoptera, Noctuidae, Noctuinae, Orthosiini). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 3 records from A new species of water mite (Acari: Hydrachnidia: Hygrobatidae) from the mantle cavity of the prosobranch gastropod Potadoma moerchi (Reeve) (Streptoneura: Thiaridae) in Nigeria. 37 records from Taxonomic review of Ablabesmyia Johannsen (Diptera: Chironomidae: Tanypodinae) from Oriental China, with descriptions of six new species. 17 records from Rediscovery of Cnemaspis nilagirica Manamendra-Arachchi, Batuwita and Pethiyagoda, 2007 (Squamata: Gekkonidae) from Kerala, India with notes on morphology and distribution. 11627497 records from Finnish Bird Ringing and Recovery Database. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 119 records from Microfossil abundance of Hole 50-416A. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 66 records from Winter Foraging Locations Of Southern Ocean Predators - sub-Antarctic islands 2008/09. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) from Ninh Binh Province, Vietnam. 103235 records from New Zealand Fungal and Plant Disease Collection (PDD). 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 5 records from A new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Cerrado-Amazonian forest transition zone, Brazil. 219 records from Umgebung der Grundschule Oderberg. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 732 records from DSMZ Collection of Plant Viruses. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 125449 records from BioGIS - Vascular plants - A. Danin's grid database. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 5895 records from Colecção Entomológica do Museu de História Natural de Maputo. 5011 records from Inventario arbóreo del Jardín Botánico Universitario del campus Meléndez de la Universidad del Valle, Santiago de Cali.. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 86 records from Oiseaux(Faune des mangroves et des zones humides du sud Togo). 724 records from Heritage Trees of Ireland. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 792 records from Nannofossil abundance of Hole 40-362. 2813 records from Amphibiens et Reptiles de Martinique (données Michel Breuil). 73 records from VFD-HH/SH: Pferdweide Lammert. 34 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 717 records from Planktic foraminifera counts of sediment core V14-81. 2215 records from Collection Polychaeta - ZSRO. 15680 records from imr_mareano_rpsledge. 26 records from Nannofossil abundance of Hole 3-14. 154 records from Elaboración de la base de datos de la colección de cepas de bacterias fitopatógenas de la Dirección General de Sanidad Vegetal. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 182 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 37 records from Planktic foraminifera abundance of Hole 73-522A. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 39 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 300 records from Plant (SMNH-PL). 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 37 records from Occurrence of mammalia relicts at site Gönnersdorf. 1855 records from The Masayo Kato Insect Collection (Hymenoptera) of The University Museum, The University of Tokyo. 58 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 23 records from Abundance of benthos infauna at station GIK23055-1. 2295 records from Invasive species - Fallopia japonica on river dikes along the river Zeeschelde, Rupel and Durme. 8 records from New species of Dugdaleiella, gen. nov., Kozloviella, gen. nov., and Pfitzneriella Viette from upper elevation Andes of Ecuador and Peru (Lepidoptera: Hepialidae). 22 records from Planktic foraminifera of sediment core GeoB1407-2. 1 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 2 records from A new species of the genus Paracypria (Crustacea: Ostracoda: Cypridoidea) from the Fiji Islands. 20891 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 14 records from Benthic foraminifera abundance of Hole 96-620. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 100 records from Nanoplankton abundance at station GeoB2006-4. 86 records from Données naturalistes de Françoise SERRE-COLLET. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 2217 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 406575 records from Herbarium of Taiwan Forestry Research Institute. 3698 records from NIWA Invertebrate Type Collection. 22918 records from Herbario de la Universidad de Sevilla, SEV-Historico. 11 records from ALP-PAGES_2017_12_18. 23 records from Ackerrain Plönhagen. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 258 records from Malawi-Histeridae-Biodiversity-Data. 1993 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 1438 records from Planktic foraminifera abundance of Hole 7-64. 9 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 22 records from Bachabschnitt der Nette (Osnabrück). 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 8 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 126 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 1 records from Oribates calcaratus. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 488557 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 11664 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 182 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 6613 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 11 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 1 records from Dinoflagellate abundance of Hole 38-343. 13486 records from CCA_pathobiome. 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 561973 records from CAS Botany (BOT). 1057 records from Palynological analysis of sediment core GeoB9508-5. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2291 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 15 records from Rare myodocopid ostracods from Mesozoic sections of Hungary: summary, revision and description of new taxa. 508 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 6 records from Abundance of benthos infauna at station GIK23065-1. 12 records from List of Lizard species recorded in Vava'u during BioRAP. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 201 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 2710188 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 835 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 201 records from Catalogue of the herbarium specimens collected from Discovery Bay and Runaway Bay, Jamaica, West Indies, 1958-1999.. 24 records from ALTERECO_2017_12_18. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 6949 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 12 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15278 records from Anymals+plants - Citizen Science Data. 47165 records from Tartu University, palaeontology collections. 1 records from A new moss salamander, genus Nototriton (Caudata: Plethodontidae), from the Cordillera de Talamanca, in the Costa Rica-Panama border region. 30 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 35 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 22435 records from UMNH Reptiles and Amphibians Collection (Arctos). 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 7 records from Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India. 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 491 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 135315 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 114 records from BIRDRACE Di-Bi-Di-Birder. 475 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 156 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 2443 records from Cnidaria MZS. 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 10 records from Benthic macrofauna abundance of sediment core 13200-017. 3916 records from Planktic foraminifera (%) of sediment core MD96-2085. 3 records from A new species of Otothyropsis (Siluriformes: Loricariidae) from the upper Río Paraná basin, Paraguay, with a discussion of the limits between Otothyropsis and Hisonotus. 144 records from Abundance of radiolaria at station LV28-42-1. 4391 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 4201 records from Gunma Museum of Natural History, Fungi Specimen. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 58 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 13979 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 5 records from Regenwasserabfangbecken Erlenbach. 38358 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 13110 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-04-1. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 27 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 9 records from Three new species of spinicaudatan clam shrimps from Australia, all from gnammas (rock pools). 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 148 records from Abundance of radiolaria at station UT99-21-2. 301 records from Birds (GNHM-BI). 1193 records from Malawi-Noctuidae-Biodiversity. 1184 records from (Table 3C) Distribution of Mesozoic nannoliths at DSDP Hole 43-384. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 50 records from Revision of the subgenus Dicranomyia (Erostrata) Savchenko, 1976 (Diptera, Limoniidae) of Japan. 3 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 4479 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 27 records from Données naturalistes de Jean-Michel SZCZYT. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 187017 records from UWFC Ichthyology Collection. 31 records from Four new genera and five new species of ‘ Heterocypris’ from Western Australia (Crustacea, Ostracoda, Cyprinotinae). 279 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 80 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 106 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Thiankoye) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 268 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 54 records from Animal Collections Of The Department of Zoology- Nasarawa State University Keffi. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 9461 records from Fern (Pteridophyta) specimens of Toyama Science Museum. 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 9 records from Calculated abundance and biomass of Ophiocten gracilis at different stations on Kolbeinsey Ridge. 153570 records from Merseyside BioBank (unverified). 11 records from Analyses of the recent components of sediment core PS1215-2. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 669 records from Abundance of large foraminifera in cores from transect HYD-01C, IODP Expedition 325. 357 records from Données d'occurrences des spécimens des plantes menacées du Sénégal conservés à l'Herbier de l'IFAN.. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91253 records from CUMV Fish Collection. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6922 records from MUST, Insecta. 637398 records from Données ONF Faune-Flore-Fonge. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 2116 records from Collection entomologique Pierre Lachiver. 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 24 records from Ostracoda abundance of Hole 48-406. 771 records from GEOECOLINK_2017_12_18. 1698 records from UTEP Herpetology Osteology (Arctos). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 85255 records from The Scottish Squirrel Database. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 46 records from Planktic foraminifera counts of sediment core V26-124. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 36 records from Selz (Ingelheim am Rhein). 398 records from Tsetse flies of East Africa update. 14 records from Nannofossil abundance of Hole 2-9. 9 records from Taxonomic review of the leafhopper genus Aconurella Ribaut (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) from Pakistan with description of three new species. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 31 records from Content of coarse fraction and G. menardii in sediment corev V25-63. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 60 records from A revision of the genus Pochytoides Berland & Millot, 1941 (Araneae: Salticidae), with descriptions of six new species. 5948 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for ODP Site 181-1123. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20755 records from pins. 1005 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 369 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 193 records from Herbario IES San Isidoro de Sevilla. 989 records from Range table from benthic foraminifers in ODP Hole 189-1170A. 7 records from Freshwater sponges from the Pampa Biome, Brazil, with description of a new species of Oncosclera. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 32 records from A new genus and species of cardinalfish (Percomorpha, Apogonidae, Sphaeramiini) from the coastal waters of Vietnam: luminescent or not?. 33 records from Pycnogonids (Arthropoda, Pycnogonida) from the Southwest Indian Ridge. 148942 records from Bell Museum lichens. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 2177 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 1672 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 22 records from Planktic foraminifera abundance of Hole 29-284A. 28916 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 1724 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 17 records from Descriptions of larvae of three species of Hydropsyche (Trichoptera, Hydropsychidae) from China. 273 records from Phytoplankton abundance at several stations in January 2005, Chipana, Chile. 147 records from NABU-Auerochsenweide. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 16282 records from Atlas der Raubfliegen Deutschlands - database. 17 records from Benthic foraminifera abundance of Hole 11-108. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 505 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 5314 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 11129 records from Royal Ontario Museum Fungarium (TRTC). 4686 records from Butterfly_conservation_2017_12_18. 75573 records from University of British Columbia Herbarium (UBC) - Algae Collection. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 137398 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 6 records from Analyses of the recent components of sediment core PS1279-1. 457 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE278. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 34224 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 203 records from Total foraminifera counts from M35/1_MSN1047. 4050 records from Range table from benthic foraminifers in ODP Hole 159-962D. 6652 records from Inventory of plant species through Benin (West Africa). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 1778 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 17 records from Benthic macrofauna abundance of sediment core 13078-013. 1075 records from Planktic foraminifera counts of sediment core RC14-35. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 36 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1543 records from Pollen record of sediment core Bokanjacko Blato 1. 26 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 167 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 4 records from Groundwater amphipods (Crustacea, Malacostraca) of India, with description of three new cavernicolous species. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 21 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 574 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 1 records from Oribates fusifer. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 258 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 5146 records from All herbarium specimens of grasses held at TAN herbarium. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 495 records from Pollen counts of sediment core GeoB9503-5. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1645 records from IFO Bacteria database. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 3 records from A new species of the genus Zographetus Watson, 1893 from China (Lepidoptera: Hesperiidae). 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 12847 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 24 records from Abundance of coccosphere-units of sediment core GIK23071-3. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 522195 records from Parc_National_de_Port_Cros_2017_12_18. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 121231 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 15 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 29 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 1645 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 99 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 28 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenopter
Keywords: GBIF; biodiversity; species occurrences